2004
DOI: 10.4315/0362-028x-67.6.1195
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Zearalenone by β-d-Glucans in the Saccharomyces cerevisiae Cell Wall

Abstract: Cell walls of yeasts and bacteria are able to complex with mycotoxins and limit their bioavailability in the digestive tract when these yeasts and bacteria are given as feed additives to animals. To identify the component(s) of the yeast cell wall and the chemical interaction(s) involved in complex formation with zearalenone, four strains of Saccharomyces cerevisiae differing in their cell wall glucan and mannan content were tested. Laboratory strains wt292, fks1, and mnn9 were compared with industrial S. cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 20 publications
6
97
0
4
Order By: Relevance
“…It was suggested that carbohydrate-rich mannoproteins or glucans might be involved in the binding, as levels of complex formation appear to be strain-and toxin-specific (Shetty and Jespersen, 2006). Raju and Devegowda (2000) attributed the binding of aflatoxins by yeast cell walls to mannan oligosaccharides, while zearalenone binding was attributed to glucan components (Yiannikouris et al, 2004). Haskard et al (2001) suggested that AFB 1 binds predominantly to carbohydrate and protein components of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that carbohydrate-rich mannoproteins or glucans might be involved in the binding, as levels of complex formation appear to be strain-and toxin-specific (Shetty and Jespersen, 2006). Raju and Devegowda (2000) attributed the binding of aflatoxins by yeast cell walls to mannan oligosaccharides, while zearalenone binding was attributed to glucan components (Yiannikouris et al, 2004). Haskard et al (2001) suggested that AFB 1 binds predominantly to carbohydrate and protein components of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of binding by β-Dglucans has been investigated by Yiannikouris and co-workers and has been discussed in several publications, e.g. (Yiannikouris et al 2004a;Yiannikouris et al 2006;Yiannikouris et al 2004b;Yiannikouris et al 2004c). It was shown that it is important to differentiate between the adsorption affinity of whole yeast cell wall and processed cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…The cell wall polysaccharides (glucan and mannan), proteins and lipids have been reported to exhibit numerous different adsorption mechanisms, e.g., hydrogen bonding, ionic or hydrophobic interaction 11 . Similarly, it has been observed that the β-D glucans isolated from S. cerevisiae cell wall is directly involved in the binding process of zearalenone 21 .…”
Section: Resultsmentioning
confidence: 99%